Aplikasi Standar TIA-942 pada Data Center Disinfolahtaau dalam Meningkatkan Layanan Sistem Informasi TNI AU - Wibisono, Lancur; Rachman, Medi; Riyanto, Tikno (Akademi Angkatan Udara, 2022)
This study analyzes the condition of the Disinfolahtaau data center whose construction was carried out in 2013 as a service for the Indonesian Air Force system. To maintain data security in the Management Information System (MIS) in the fields of operations, logistics, personnel, and management, currently there are still problems with data center operations that run 1 x 24 hours. For this reason, it is necessary to compare the condition of the data center with the data center standards that have been made with reference to the TIA-942 International data center standard. The purpose of this study is to analyze the condition of the Disinfolahta or data center in several aspects, namely the architectural aspect of the building, the electrical aspect, the telecommunication aspect and the mechanical aspect that implements it by applying the TIA-942 standard. The data of this research were collected through informants based on the methods of interview, observation and documentation study. Then the data was analyzed using the Countance Stake's Model analysis. Each aspect in the Countance Stake's Model is then analyzed the actual conditions of each aspect which are combined to produce conclusions about future policies in the Disinfolahtaau data center condition. The results showed that the results of the analysis of the Disinfolahtau data center from the architectural aspect of the building, the electrical aspect, the telecommunication aspect and the mechanical aspect of the data center construction in 2013. With some aspect analysis on the Disinfolahtaau data center will provide the real condition of the capabilities and capacity of the data center so as to know the current conditions. This is so that we can find out problems in the condition of the data center, this has an impact after if some deficiencies are corrected in the Disinfolahtaau data center. However, it can have a negative impact if the current condition of the data center is not immediately repaired, it will interfere with the non-operation of the data center so that information system services will be disrupted in providing information system services within 1 x 24 hours in operation. Looking at the current situation and conditions compared to the initial development in 2013, it is necessary to develop the Disinfolahtaau data center for evaluation and revitalization in improving the optimal Indonesian Air Force information system services.